1499 Study of the Pattern of Cerebral Palsy among Children in Alexandria, Egypt. (October 2012) - Abdeldayem, HH; Kamel, F; Khalil, M; Elmansy, S
Abstract : Cerebral Palsy (CP) is the commonest neuromotor impairment in childhood. In recent years, there has been mounting changes in CP pattern. Advances in perinatal and newborn cares have been responsible for these changes. Advances in medical techniques have been also responsible for the extension of the life of CP children to an age of diagnosis and classification. Over the last several years, our knowledge about CP has been substantially improved, but much works still remains. Despite of its importance, the problem is largely ignored in developing countries including Egypt. The aim of our study was arranged for: Giving a recent comprehensive study about CP patterns among CP infants and children attending Alexandria University Children's Hospital over a period of one year (2010–2011) including: clinical types, topographic types, etiology, and severity. Identifying common associated impairments of CP cases. Comparing our results with other similar studies in Egypt and other developing and developed countries.